Development and content validation of two new patient-reported outcome measures for endometriosis: the Endometriosis Symptom Diary (ESD) and Endometriosis Impact Scale (EIS) - Adam Gater; Fiona Taylor; Christian Seitz; Christoph Gerlinger; Kamonthip Wichmann; Claudia Haberland (SpringerOpen, 2020)
Abstract Background Endometriosis is a common, chronic, impactful condition in women of reproductive age. In the absence of established sensitive and specific biomarkers, disease severity is determined by patient-reported symptoms and impacts. This article details the development of two new patient-reported outcome (PRO) measures designed to assess efficacy endpoints in clinical studies: The Endometriosis Symptom Diary (ESD) and the Endometriosis Impact Scale (EIS). Methods The ESD and EIS were developed according to best practice and scientific standards (including the Food and Drug Administration (FDA) PRO Guidance) and with extensive input from women with surgically-confirmed endometriosis. Research included: a review of published qualitative literature; concept elicitation interviews in the US, Germany and France (n = 45) to explore the experiences of women with endometriosis and to inform ESD and EIS development; and cognitive interviews in the US and Germany (n = 31) to assess relevance and understanding of the ESD and EIS and usability of administration using an electronic handheld device. The FDA and the European Medicines Agency (EMA) as well as PRO and clinical experts were consulted throughout the process. Results Pelvic pain was identified as the most frequent, severe and bothersome symptom for women with endometriosis. Pain was reported to be greatest during menstruation (dysmenorrhea) and during or after sexual intercourse (dyspareunia). Pain resulted in significant impairments in physical activities, work/study, social/leisure activities, household activities and sexual functioning. All women highlighted the emotional impact of endometriosis. Descriptions of pain and associated impacts were largely consistent across participants from the US and Europe, with the most notable differences being the words used to describe the location of pain (e.g., 'pelvis' vs. 'abdomen'). Testing during cognitive interviews indicated that the ESD and EIS were well understood and consistently interpreted. Furthermore, all participants found the ePRO devices easy to use and no issues regarding visual presentation, selection of responses or navigation were identified. Conclusions Evidence from extensive qualitative research supports the content validity of the ESD and EIS as patient-reported measures of the disease-defining symptoms of endometriosis and the associated impact on women's lives. Future research will seek to establish the measurement properties of the measures.